Contingent Valuation of Woodland-Owner Private Amenities in Spain, Portugal, and California. - Campos, Pablo; Oviedo, José L.; Caparros, Alejandro; Huntsinger, Lynn; Coelho, Inocencio (Rangeland Ecology & Management, 2009)
Most of the Mediterranean woodlands in Spain, Portugal, and California are managed as agrosilvopastoral enterprises, producing some combination of livestock, wood, cork products, and crops, as well as wildlife habitat and diverse environmental services. Private amenity benefits to landowners have been suggested as an explanation for high land prices and the persistence of such rangeland enterprises despite apparently marginal cash returns. In this study, private amenity values are estimated using a contingent valuation technique in surveys of private woodland owners as part of five case studies, using a design developed to separate landowner amenity income and capital values. Nonindustrial private landowners were asked about the maximum amount of money that they were willing to give up (to pay) before selling their property to invest in more commercially profitable assets, and the proportion of the market price of their woodland that they think is explained by privately consumed amenities. Amenity values were found to be relevant because, in all cases, landowners were willing to pay > €120 · ha−1 · yr−1, at 2002 prices, and attributed > 30% of land market price to amenities. These values represent an amenity profitability rate > 2% in all case studies. The data analysis shows some similarities, but mostly divergences, in the different land-simulated and amenity-simulated markets.
Keywords: agroforestry systems; environmental economics; environmental services; Mediterranean woodlands; private ownership; Stated Preferences

Contingent Valuation of Woodland-Owner Private Amenities in Spain, Portugal, and California. - Campos, Pablo; Oviedo, Jose L; Caparros, Alejandro; Huntsinger, Lynn; Coelho, Inocencio (Rangeland Ecology & Management, 2009)
Most of the Mediterranean woodlands in Spain, Portugal, and California are managed as agrosilvopastoral enterprises, producing some combination of livestock, wood, cork products, and crops, as well as wildlife habitat and diverse environmental services. Private amenity benefits to landowners have been suggested as an explanation for high land prices and the persistence of such rangeland enterprises despite apparently marginal cash returns. In this study, private amenity values are estimated using a contingent valuation technique in surveys of private woodland owners as part of five case studies, using a design developed to separate landowner amenity income and capital values. Nonindustrial private landowners were asked about the maximum amount of money that they were willing to give up (to pay) before selling their property to invest in more commercially profitable assets, and the proportion of the market price of their woodland that they think is explained by privately consumed amenities. Amenity values were found to be relevant because, in all cases, landowners were willing to pay >€120 · ha−1 · yr−1, at 2002 prices, and attributed > 30% of land market price to amenities. These values represent an amenity profitability rate > 2% in all case studies. The data analysis shows some similarities, but mostly divergences, in the different land-simulated and amenity-simulated markets.
Keywords: agroforestry systems; environmental economics; environmental services; Mediterranean woodlands; private ownership; Stated Preferences

Would you choose your preferred option? Comparing choice and recoded ranking experiments - Caparros, Alejandro; Oviedo, Jose L; Campos, Pablo (AMERICAN JOURNAL OF AGRICULTURAL ECONOMICS, 2008)
Previous research has shown that results from a choice experiment are statistically different from those obtained from a ranking experiment that is recoded and treated as a choice experiment using only the first rank. By avoiding some of the shortcomings of previous comparisons, we obtain the opposite results using data from the valuation of a cork oak reforestation program in the south of Spain. Structural models and welfare estimations are statistically indistinguishable irrespective of the use of parametric or bootstrapping tests. Further, we employ follow-up questions and subsample analysis to test whether divergences appear when potential effects are isolated.
Keywords: choice modeling; conjoint analysis; cork oak reforestation; environmental preferences; recoded ranking

Measuring total sustainable incomes from multifunctional management of Corsican Maritime Pine and Andalusian Cork oak Mediterranean forests - Campos, Pablo; Bonnieux, François; Caparros, Alejandro; Paoli, Jean-Christophe (Journal of Environmental Planning and Management, 2007)
Abstract Enough advances have recently been made in income accounting theory to recommend that environmental services accruing either to the forest owner or to the general public should be included in the forest accounting system. In this study, the results of two case studies, one in Bonifatu, Corsica (France) and the other in Alcornocales, Andalusia (Spain), show that private environmental services provide the majority share of social total sustainable income in Alcornocales (29%), whereas public environmental services are the most relevant in Bonifatu (32%). The social total sustainable income measured by the agroforestry accounting system is, respectively, 1.6 and 2.4 times higher than the income estimated by economic accounts for forestry in Alcornocales and Bonifatu forests.
doi: 10.1080/09640560601048424
Keywords: accounting system; benefits; Bonifatu; environmental services; Los Alcornocales; management (voyant); market price; sustainable income; Values

Measuring total sustainable incomes from multifunctional management of Corsican Maritime Pine and Andalusian Cork oak Mediterranean forests - Campos, Pablo; Bonnieux, François; Caparros, Alejandro; Paoli, Jean-Christophe (Journal of Environmental Planning and Management, 2007)
Abstract Enough advances have recently been made in income accounting theory to recommend that environmental services accruing either to the forest owner or to the general public should be included in the forest accounting system. In this study, the results of two case studies, one in Bonifatu, Corsica (France) and the other in Alcornocales, Andalusia (Spain), show that private environmental services provide the majority share of social total sustainable income in Alcornocales (29%), whereas public environmental services are the most relevant in Bonifatu (32%). The social total sustainable income measured by the agroforestry accounting system is, respectively, 1.6 and 2.4 times higher than the income estimated by economic accounts for forestry in Alcornocales and Bonifatu forests.
doi: 10.1080/09640560601048424doi: 10.1080/09640560601048424The following values have no corresponding Zotero field: publisher: Routledge
Keywords: accounting system; benefits; Bonifatu; environmental services; Los Alcornocales; management (voyant); market price; sustainable income; Values

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
The following values have no corresponding Zotero field: periodical: Handbook Of Operations Research In Natural Resources electronic-resource-num: 10.1007/978-0-387-71815-6
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model